Cell-Based Therapies for Joint Disease in Veterinary Medicine: What We Have Learned and What We Need to Know - Bogers, Sophie Helen (Frontiers in Veterinary Science, 2018)
Biological cell-based therapies for the treatment of joint disease in veterinary patients include autologous conditioned serum, platelet rich plasma and expanded or non-expanded mesenchymal stem cell products. This narrative review outlines the processing and known mechanism of action of these therapies, and reviews current pre-clinical and clinical efficacy in joint disease in the context of the processing type and study design, as well as the significance of variation for biologic activity and consequently regulatory approval. There is significant variation in study outcomes for canine and equine cell-based products derived from whole blood or stem cell sources like adipose and bone marrow. Variation can be attributed to altering bio-composition due to factors including preparation technique and source. Additionally, study design factors like selection of cases with early vs. late stage osteoarthritis or with intra-articular soft tissue injury influence outcome variation. In this under-regulated field, variation raises concerns for product safety, consistency and efficacy. Cell-based therapies used for osteoarthritis meet the FDA’s definition of a drug; however, researchers must consider their approach to veterinary cell-based research to meet future regulatory demands. This review explains the USA’s FDA guidelines as an example pathway for cell-based therapies to demonstrate safety, effectiveness and manufacturing consistency. An understanding of the variation in production consistency, effectiveness and regulatory concerns is essential for practitioners and researchers to determine what products are indicated for treatment of joint disease and tactics to improve the quality of future research.